Digital financial inclusion in WAEMU countries: does the development of digital financial services stimulate economic growth? - Dianda, Pousbila (International journal of economic perspectives, 2025)
This study analyzes the effect of digital financial inclusion on economic growth in WAEMU countries. Using data from BCEAO (2024) and the World Bank (2024) for the period 2011-2022, we employ the two-stage system generalized method of moments (System GMM). This approach allows us to take into account the endogeneity of lagged variables and to correct for biases linked to the omission of unobservable but time-constant variables. The results show that digital financial inclusion stimulates economic growth through several mechanisms. It encourages the mobilization of domestic savings and directs resources toward productive investment, thus contributing to capital accumulation and job creation. It also enables households to invest in health and education, boosting human capital and long-term productivity. Furthermore, the development of digital finance improves economic governance by facilitating the traceability of financial flows, tax collection and the targeted distribution of public aid, strengthening the State’s ability to support inclusive growth. Sustainable growth requires a multidimensional approach. It is essential to extend the infrastructure of digital financial services, particularly in rural and peri-urban areas, to reduce inequalities in access. Moreover, the development of digital technologies and platforms must be encouraged while guaranteeing the security of transactions, the protection of personal data and the interoperability of systems. Finally, strengthening financial and digital education remains crucial to transforming access to technologies into effective financial inclusion.